1983
DOI: 10.1056/nejm198312223092503
|View full text |Cite
|
Sign up to set email alerts
|

Use of Single Voided Urine Samples to Estimate Quantitative Proteinuria

Abstract: Quantitation of urinary protein excretion is used extensively for diagnostic and prognostic purposes and to assess the effects of therapy. The method most commonly used to measure urinary protein relies on 24-hour urine collections, which are time consuming, cumbersome, and often inaccurate. We reasoned that the urinary protein/creatinine ratio in a single voided urine sample should correlate well with the quantity of protein in timed urine collections. In a study of 46 specimens we found an excellent correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
363
4
25

Year Published

1984
1984
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 666 publications
(404 citation statements)
references
References 8 publications
7
363
4
25
Order By: Relevance
“…This is particularly important for patients who have RCC or are receiving high-dosage bevacizumab, who are at high risk for high-grade proteinuria. Measurement of spot urine protein and creatinine is convenient and reliable 36 and may be used to monitor proteinuria instead of cumbersome 24-hour urine protein assay. Preventive measures may include the optimal control of hypertension and the use of angiotensin-converting enzyme inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for patients who have RCC or are receiving high-dosage bevacizumab, who are at high risk for high-grade proteinuria. Measurement of spot urine protein and creatinine is convenient and reliable 36 and may be used to monitor proteinuria instead of cumbersome 24-hour urine protein assay. Preventive measures may include the optimal control of hypertension and the use of angiotensin-converting enzyme inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A methodological limitation of our study is that at the baseline examination, performed more than 20 years ago, we measured total urinary protein concentration from spot urine samples with the Coomassie brilliant blue method, instead of using a specific assay for albumin [46][47][48] which constitutes about one-half of total urinary protein [49]. Correlation of albuminuria with proteinuria has been previously documented with convergence toward the line of unity with increasing degrees of proteinuria [50].…”
Section: Discussionmentioning
confidence: 99%
“…The urinary albumin-to-creatinine ratio was used to estimate UAE in the present study. Several studies (17)(18)(19)(20) have shown good agreement between albumin excretion measured in this fashion and direct measurement of short-term urinary albumin excretion or of overnight or 24-h urinary albumin excretion. The present study showed that the mean UAE level in hypertensive patients in whom BP was controlled by treatment with GCBs was 39.4 ± 6.2 mg/g Cr (n = 63).…”
Section: Discussionmentioning
confidence: 99%